Experience and role of Italian nurses working in genetic clinics: a descriptive phenomenological qualitative study - Lea Godino; Camilla Elena Magi; Carla Bruzzone; Stefano Bonora; Marco Seri; Liliana Varesco; Daniela Turchetti (BMC Nursing)
Abstract Background In several countries, the role of the genetic nurse has developed over decades, becoming well-recognized and integrated into healthcare systems. In contrast, in Italy, this role is still emerging, with no formal legal recognition and limited awareness among healthcare professionals and hospital administrators. Given this context, it is crucial to assess how the role and activities of nurses in genetic clinics in Italy are perceived. Methods Phenomenological qualitative study was performed. Three focus groups and one individual interview were conducted to collect data between April and November 2022 and transcribed verbatim. Phenomenological analysis was used to provide a comprehensive description of the overall thematic map and to interpret the data. Results A purposive sample of 14 Italian nurses with working experience in genetic clinics were recruited for interviews. Three themes were identified: (a) Education, (b) Working in genetic clinics, and (c) Acknowledgement of genetic nurse role. The absence of genetics education in nursing programs has led to on-the-job training in this field. The activities performed were unclear since they were neither standardized nor recognized. The role of the genetic nurse was not acknowledged, and in Italy, nurses trained in genetics did not have the opportunity to choose their recruitment as it was not voluntary. Conclusions This evidence highlights the need for formally recognizing the role of the genetic nurse in Italy. This could be achieved through the definition of standard activities and the implementation of formal education in genetics and genomic fields.